¨El proceso andragógico en las personas privadas de la libertad de la etapa de mediana seguridad del proyecto EBJA Monseñor Leónidas Proaño del Centro de Rehabilitación Social (CRS) Sierra Centro Cotopaxi¨ - Castillo Ordoñez, Nelly Carina (2021)
This research makes an analisis and an evaluation about how to contribute in the formation of people private of liberty in the medium security stage from the EBJA Monseñor Leonidas Proaño Project of General Basic Education From the Centro de Rehabilitación Social (CRS) Sierra Centro Cotopaxi, likewise, it makes emphasis in the need to achieve the objective to elaborate an andragogic plan for the deprived people from the medium security stage of the EBJA Monseñor Leonidas Proaño Project of General Basic Education from the Centro de Rehabilitación Social Sierra Centro Cotopaxi. The most usual methodology in the fields of Social and humanistic Sciences will help us to determine that when an andragogic strategy is designed , the results will be efficient , improving the teaching process inside the classroom , through an applied modality which will be reflected in the teacher’s ideology and transformation with a descriptive purpose , through the deductive, analytical and modeling method we will achieve very positive results within the andragogic process, bringing an excellent teachers and students’ development inside the CRS, thanks to the use of Andragogic stategies , improving in this way the teaching process in the CRS education, which makes Andragogy a doctrine which must be used every day in the young and adult people deprived of liberty. The use of new andragogic strategies, such as, learning through dramatizations or mimic process has been taken as a frequent necessity, mainly in the teaching process by the teacher, in this way, it allows the student to be the actor and participant of the learning, where responsibilities are atributted to participate, work as a team, seek an organization and plannification for the solution of a problem.